Experimental and statistical exploring for mixed-mode (I&II) fracture behavior of cement emulsified asphalt mortar under freeze–thaw cycles and aging condition. (December 2022) - Najjar, Shima; Mohammadzadeh Moghaddam, Abolfazl; Sahaf, Ali; Aliha, M.R.M.
Highlights: Effects of freeze–thaw cycles and aging on mixed-mode I/II fracture of CEAM were investigated. Experiments were performed in three modes of loading; (I), (II), and (I/II). d -optimal RSM suggested to fracture 864 SCB specimens with 16 mix designs at different C, A/C, and W/C. Freeze-thaw cycles are more detrimental in reducing mode II fracture energy. Aging has a more damaging impact on the pure tensile fracture. Statistical models were developed for the relationship between FER and mix design variables. A/C for mode I, and C for mode II and the mixed-mode I/II, had the greatest impact on FER of freeze/thaw, and A/C for that of aging. Abstract: This study has been investigated the effect of freeze–thaw cycles and aging condition on the pure mode I, pure mode II and mixed-mode I/II fracture resistance of Cement Emulsified Asphalt Mortar (CEAM). The experiments were conducted on SCB specimens designed with 16 randomized mix designs with different cement contents (C), asphalt-to-cement ratios (A/C), and water-to-cement ratios (W/C) using the d -optimal response surface methodology. The specimens were divided into three groups: control specimens (n = 144), aged specimens (n = 144), and specimens subjected to 1, 3, 5, and 10 freeze–thaw cycles (n = 576). The experiments were performed in three modes of loading: pure tensile (I), pure shear (II), and mixed-mode tensile-shear (I/II). To assess the impact of freeze–thaw and aging damage on fracture properties, the Fracture Energy Ratio (FER) was defined as the ratio of fracture energy of the damaged/conditioned specimen to that of the corresponding control specimen. Then, a number of statistical models were developed for the relationship between FER and mix design variables (A/C, W/C, and C). The results showed that the application of freeze–thaw cycles reduced the fracture energy of CEAM in all three modes. The independent variable with the greatest impact on fracture energy changes was A/C for the pure tensile mode, and C for the pure shear mode and the mixed-mode tensile-shear. The initial freeze–thaw cycles were found to have a greater impact on fracture energy than later cycles. Also, freeze–thaw cycles are more detrimental in reducing mode II fracture energy than mode I and mixed-mode I/II fracture energies and therefore have a more damaging impact on the pure shear fracture properties of CEAM. Aging also reduced the fracture energy of CEAM in all three modes; an effect that was most greatly influenced by the amount of asphalt in the mortar composition. Aging had a greater impact on mode I fracture energy than mode II and mixed-mode I/II fracture energies.